Exploring the impact of product quality and cash on delivery on consumer purchase decisions for fashion products - Amin, Mat; Firdaus, Rahmad; Nugroho, Fithriawan; Suhardi, Suhardi; Rejeki, Nadia Sri (Institute of Computer Science (IOCS), 2024)
This study aims to investigate the effect of product quality on purchase decisions through cash on delivery in the fashion industry. The research was conducted through a survey with 228 respondents who had made purchases through cash on delivery in the past six months. The data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results showed a significant and positive effect of product quality on purchase decisions through cash on delivery in the fashion industry. This finding suggests that consumers who perceive high product quality are more likely to make a purchase decision through cash on delivery in the fashion industry. The study also indicates that the moderating effect of cash on delivery should be considered in future research on the relationship between product quality and purchase decisions in the fashion industry. This study contributes to the existing literature by providing empirical evidence on the effect of product quality on purchase decisions through cash on delivery in the fashion industry. Fashion retailers can use the results to improve their product quality and cash-on-delivery services, potentially increasing consumer purchase decisions and satisfaction.